Hydrological Environments for Vein Mineralisation in the Hauraki Goldfield, New Zealand (The Australasian Institute of Mining and Metallurgy, 1991)
The epithermal Au-Ag deposits of the Hauraki Goldfield have formed in the convergent plate margin setting of the Coromandel Volcanic Zone (CVZ). The deposits form as siliceous lodes in the upper parts of geothermal systems associated with andesitic and rhyolitic volcanism. Two types of low sulphidation epithermal mineralisation are recognised in these volcanic terranes. Vein deposits within the rhyolitic terrane in the east and south of the CVZ (Whitianga Province) are typified by Chalcedonic Silica-Adularia-Illite type mineralisation. The veins are hosted by both rhyolite-dacite volcanic rocks and the underlying andesitic basement. The mineralisation formed by episodic violent decompressional boiling of deeply circulating meteoric water, with some magmatic fluid contribution; this boiling was associated with hydraulic fracturing and hydrothermal eruptions in geothermal systems where the piezometric surface of the deep geothermal reservoir lay near-surface. Such episodic boiling provides chalcedonic veining, banding and brecciation textures, adularia stability, bladed calcite, and extreme loss of H2S gas from the fluid to cause major gold deposition.   Crystalline Quartz-Illite-(Adularia-Kaolinite) type mineralisation is widespread in the andesitic terrane forming the northern and western portions of the CVZ (Kuaotunu Province). There is a spatial association with weak mineralisation of the high sulphidation (Vuggy Silica-Alunite-Kaolinite-Illite) epithermal type and porphyry eu-Au type. Crystalline Quartz mineralisation is probably formed by the mixing of shallow acidic groundwaters with the ascending deep geothermal fluid in geothermal systems beneath andesitic stratovolcanoes. The piezometric surface to the deep geothermal reservoir in these systems is likely to lie at considerable depth, with acidic gases rising from the geothermal reservoir condensing within the overlying vadose zone. The cooling effect, oxidation and pH decrease accompanying mixing apparently overcomes the dilution effect, and results in quartz deposition, illite (and locally kaolinite) alteration, and precipitation of gold. A high level of base-metal sulphide precipitation also enhances gold deposition. Violent boiling of the mixing fluids may occur at local structural dilation sites, producing high grade "bonanza" gold mineralisation.